Farm characteristics related to on-farm cow mortality in dairy herds: a questionnaire study. (1st July 2014) - Alvåsen, K.; Roth, A.; Jansson Mörk, M.; Hallén Sandgren, C.; Thomsen, P. T.; Emanuelson, U.
Abstract : Dairy cow mortality is an important animal welfare issue that also causes financial losses. The objective of this study was to identify farm characteristics and herd management practices associated with high on-farm cow mortality in Swedish dairy herds. A postal questionnaire was sent to farmers that had either high or low mortality rates for 3 consecutive years. The questionnaire consisted of five sections: 'About the farm', 'Milking and housing', 'Feeding', 'Routines' and 'Lame and sick cows'. A total of 145 questionnaires were returned (response rate=33%). Ten of the 77 characteristics investigated met the inclusion criteria for multivariable analysis. The final logistic regression model included: herd size, breed, use of natural service bull, bedding improvement frequency and pasture system. Herds with Swedish Holstein as the predominant breed (odds ratio (OR) 22.9, 95% confidence interval (CI) 5.2 to 101.8) or with mixed breeds (OR 5.5, 95% CI 1.7 to 17.5) had a greater risk of being high mortality herds than herds that were predominantly Swedish Red (OR 1). Herds larger than 100 cows (OR 19.6, 95% CI 3.5 to 110.4) and herds with 50 to 99 cows (OR 13.8, 95% CI 3.2 to 60.6) had greater risk of mortality than herds numbering 35 to 50 cows (OR 1). Being a high mortality herd was also associated with having cows on exercise lots during the summer season (OR 3.6, 95% CI 1.3 to 9.9) compared with on pasture. A missing answer on the question of bedding improvement frequency was associated with high mortality herds. Overall, this study suggests that characteristics that are related to intensification of the dairy industry are also associated with high on-farm mortality of dairy cows.